Aortic Intramural Hematoma Mimicking Acute Coronary Syndrome - Zainal Fathurohim; Novi Kurnianingsih; Djanggan Sargowo; Heny Martini (Universitas Brawijaya, 2023)
Abstract :Type A Aortic intramural haematoma (IMH), a variant form of classic aortic dissection, has been accepted as an increasingly recognised and potentially fatal entity of acute aortic syndrome.It is a very dangerous, fatal, and emergency condition. It is very important to recognize the symptoms of acute aortic syndrome related to appropriate management Case IllustrationA 52 year old man patient suffered from chest pain with moderate intensity while he was working at home. It was sharp , tear-like sensation, in the middle of the chest radiated to the back, accompanied with cold sweating, and did not relieve by rest. Because of this condition he brought to hospital. From examination at Emergency room, he had cardiomegaly, aortic dilatation. From the Electrocardiography an st elevation at V1-V2 and T inverted V4-V6 precordial lead,I aVL extremities lead and slightly elevated cardiac enzymes with risk factors for active smoking and uncontrolled hypertension. Initially he was suspected of having acute coronary syndrome with differential diagnose acute aortic syndrome. To exclude the diagnose he had underwent cardiac catheterization, the cardiologist in charge suspicious this patient with aortic dissection because of trapping contrast durante procedure and coronary minor disease. For a better diagnosis, transtransthoracic echocardiography and Aortic Computed Tomography angiography was performed on the patient which confirmed the evidence of dissection. After being diagnosed, we treat the patient as an acute aortic syndrome and we stabilize the patient's condition. The patient was planned for cardiac surgery DiscussionAcute aortic syndrome, which includes Acute Aortic Dissection, Intramural Hematoma and penetrating aortic ulcer, is difficult to diagnosed. Aortic intramural hematoma, which is one of the acute aortic syndromes, is characterized by the presence of a hematoma in the medial layer of the aortic wall without the appearance of an intimal tear. The incidence of intramural hematoma differs slightly from that of aortic dissection syndrome. Patients with intramural hematomas often occur in older patients, more often with aortic aneurysmsThe patient receive treatment aggressively to control blood pressure by administering a non-dihydropyridine calcium channel blocker intravenously and then beta blocker, angiotensin II receptor blockers, was also needed. Acute aortic syndrome, where an intramural aortic hematoma can present with varying symptoms of varying severity, which can lead to misdiagnosis and delay in cases of life-threatening disease. In the case of our patient, who had strong cardiac risk factors, His initial presentation described an acute myocardial infarction; the diagnosis was made after CT scan was performed and the patient remained stable ConclussionComplaints of chest pain due to symptoms of acute aortic syndrome are very important to be recognized immediately because they need proper management. Complaints in this syndrome have similarities with complaints in acute coronary syndrome, pulmonary embolism and others. Patients with aortic intramural hematoma are at high risk for developing periaortic hematoma and hemorrhagic pericardial effusion. In patients with an intramural aortic hematoma, Stanford A, the most appropriate management is surgical technique. Initial management of blood pressure control, heart rate and anti-pain can be given. In this case, the choice of a combination of surgery with endovascular may be a logical choice of therapyKeywordAortic Intramural Hematoma, Acute aortic syndrome